PENGARUH KUALITAS PELAYANAN TERHADAP KEPUASAN PELANGGAN DI GRAND HYATT HOTEL JAKARTA - Darwin Raja Unggul Saragih; Risky Septiani (Panorama Nusantara, 2019)
The purpose of this study was to determine the influence of service quality on customers satisfaction at Grand Hyatt Hotel Jakarta. The targeted population in this study are regular guests of Grand Hyatt Hotel Jakarta with the number of samples and giving directly questionaries to 100 guests by purposive sampling technique. The research method that used in this research were descriptive and quantitative. Data was analyzed by SPSS-software. Analysis of data used in this research are linear regression multiple, validity test, reliability test, assumsion classic test (normality, heteroskedasticity, multikoliniearity, and the linearity). While the testing of hypotheses by the F test, the results of the significant by t-test, partial correlation analysis and coefficients of determination (R2. The results of this study state that service quality boyh partially and silmutaneously have significantly influenced on the customer satisfaction at Grand Hyatt Hotel Jakarta. However the partial one all in weak influence.